2021
DOI: 10.1084/jem.20201803
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of classical neutrophils and polymorphonuclear myeloid-derived suppressor cells in cancer patients and tumor-bearing mice

Abstract: In this study, using single-cell RNA-seq, cell mass spectrometry, flow cytometry, and functional analysis, we characterized the heterogeneity of polymorphonuclear neutrophils (PMNs) in cancer. We describe three populations of PMNs in tumor-bearing mice: classical PMNs, polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs), and activated PMN-MDSCs with potent immune suppressive activity. In spleens of mice, PMN-MDSCs gradually replaced PMNs during tumor progression. Activated PMN-MDSCs were found only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
163
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(170 citation statements)
references
References 58 publications
7
163
0
Order By: Relevance
“…Our results show that ASC can induce features of PMN-MDSC in mature neutrophils: low density, increased LOX-1 expression, and T-cell suppressor function. These results are consistent with the growing understanding of granulocyte diversity in the TME (50,51), and the notion of granulocyte subsets acquiring suppressor function through distinct pathways that include abnormal granulopoiesis (bona fide PMN-MDSC) and signaling pathways induced in the TME that render normal mature neutrophils suppressive.…”
Section: Low-density Neutrophils May Be a General Response To Activation By Microbial Products Orsupporting
confidence: 87%
“…Our results show that ASC can induce features of PMN-MDSC in mature neutrophils: low density, increased LOX-1 expression, and T-cell suppressor function. These results are consistent with the growing understanding of granulocyte diversity in the TME (50,51), and the notion of granulocyte subsets acquiring suppressor function through distinct pathways that include abnormal granulopoiesis (bona fide PMN-MDSC) and signaling pathways induced in the TME that render normal mature neutrophils suppressive.…”
Section: Low-density Neutrophils May Be a General Response To Activation By Microbial Products Orsupporting
confidence: 87%
“…PMN-MDSCs are considered to represent a subset of neutrophils with immunosuppressive functions that are generated and accumulated during tumor development [35,139,140]. It was reported that TAN1 possess the characteristics of classical neutrophils, whereas TAN2 have features of PMN-MDSCs [14] (Table 1).…”
Section: Tumor Suppressive Properties Of S100a8/a9 Proteins In Pmn-mdscsmentioning
confidence: 99%
“…However, recent evidence suggests that different PMN populations coexist in tumor bearing mice and cancer patients. In this context, three different PMN populations were found infiltrating the tumor: 30% corresponded to neutrophil-like PMNs, 16% classical PMN-MDSCs and 55% were activated PMN-MDSCs ( Veglia et al, 2021 ).…”
Section: Neutrophil Subsets and Characterizationmentioning
confidence: 99%
“…Genetically, the three sub-populations show distinct gene expression profiles, ranging from non-suppressive PMNs, to immature/suppressive PMN-MDSCs (both found mainly in the spleen of healthy or tumor-bearing mice), and high chemokine/ER stress responses in activated PMN-MDSCs, residing mainly in tumors ( Veglia et al, 2021 ). Interestingly, CD14 was shown to be a good marker of activated PMN-MDSCs in tumor-bearing mice, which was also associated with poor prognosis in cancer patients ( Veglia et al, 2021 ). Supporting these findings, Zilionis et al (2019) described similar neutrophil populations.…”
Section: Neutrophil Subsets and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation